Striving for Excellence: Enhancing Madrasah Quality through Analysis of Science Competition Questions and ICT-Driven Learning Transformation - Ahmad Abtokhi; Hisyam Fahmi (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
This article focuses on a community service program designed to enhance the quality of madrasah education in the Malang Regency and City regions, East Java, Indonesia. The program encompasses various aspects, such as integrating Islamic values into Science Competition Questions (KSM IPA), utilizing virtual laboratories in science and mathematics learning, and implementing Information and Computer Technology (ICT) in teaching. Educational challenges have grown complex in an era marked by globalization and technological advancements. The program aims to improve critical thinking skills and student competitiveness by integrating Islamic values into science education. The article discusses the program's objectives, methods employing the Asset-Based Community Development (ABCD) approach, coordination, training, and post-mentoring evaluation. The positive participant response and measurable impact reflect the relevance of enhancing teacher competence and technology integration. This initiative aligns with the region's efforts to provide quality education and foster student development.